Penurunan Tekanan Darah Menggunakan Terapi Akupresur Pada Pasien Hipertensi - Siti Musalamah; Abi Muhlisin (Jurnal Keperawatan Florence Nightingale, 2025)
Hypertension is a chronic disease that cannot be cured, but can be controlled. Acupressure therapy is one of the therapies to control blood pressure in hypertension to avoid complications. This study aims to analyze the application of acupressure therapy to reduce blood pressure in hypertension sufferers. This article was written using a literature review obtained from Garuda, Science Direct, and PubMed, covering the period between 2019 and 2024, in Indonesian and English. A total of 8 articles were reviewed after the search results. All of these articles stated that acupressure therapy can lower blood pressure and can be done at several points on the body. Stimulating nerve waves to smooth blood flow and lower blood pressure can be done by applying pressure to acupuncture points on the body. The application of acupressure therapy in an effort to lower blood pressure in patients with hypertension is considered quite significant and effective. Acupressure therapy can also help lower heart rate, improve sleep quality, and reduce stress levels.